The iCanCope pain self-management application for adolescents with juvenile idiopathic arthritis: a pilot randomized controlled trial. (2nd July 2020) - Lalloo, Chitra; Harris, Lauren R; Hundert, Amos S; Berard, Roberta; Cafazzo, Joseph; Connelly, Mark; Feldman, Brian M; Houghton, Kristin; Huber, Adam; Laxer, Ronald M; Luca, Nadia; Schmeling, Heinrike; et al.
Abstract: Objectives: To evaluate the feasibility and preliminary effectiveness of iCanCope with Pain ( iCanCope ), a smartphone-based pain self-management program, in adolescents with JIA. iCanCope featured symptom tracking, goal-setting, pain coping skills and social support. Methods: A two-arm pilot randomized controlled trial was used to evaluate the iCanCope app compared with a version with symptom tracking only. Primary (feasibility) outcomes were: participant accrual/attrition rates, success of app deployment, acceptability and adherence. Secondary (preliminary effectiveness) outcomes were: pain intensity, pain-related activity limitations and health-related quality of life. Outcomes were assessed at baseline and 8 weeks. Adherence was defined as the proportion of completed symptom reports: 'low' (≤24%); 'low-moderate' (25–49%); 'high-moderate' (50–75%); or 'high' (76–100%). Linear mixed models were applied for preliminary effectiveness analyses as per intention-to-treat. Results: Adolescents ( N = 60) were recruited from three paediatric rheumatology centres. Rates of accrual and attrition were 82 and 13%, respectively. Both apps were deployed with high success (over 85%) and were rated as highly acceptable. Adherence was similar for both groups, with most participants demonstrating moderate-to-high adherence. Both groups exhibited a clinically meaningful reduction in pain intensity (≥1 point) that did not statistically differ between groups. There were no significant changes in activity limitations or health-related quality of life. Conclusion: The iCanCope pilot randomized controlled trial was feasible to implement in a paediatric rheumatology setting. Both apps were deployed successfully, with high acceptability, and were associated with moderate-to-high adherence. Preliminary reductions in pain intensity warrant a future trial to evaluate effectiveness of iCanCope in improving health outcomes in adolescents with JIA. Trial registration: ClinicalTrials.gov identifier: NCT02764346.